From Stage to Civic Life Reyog Ponorogo Influence on Social Norms Legal Consciousness and Education in Indonesia - Utami, Prihma Sinta; Marzuki; Rukiyati (NAJAHA, 2024)
This article explores the potential of Reyog Ponorogo, a local Indonesian cultural narrative, to nurture positive citizenship qualities. The concept of citizenship and its associated character traits are crucial for a functioning democracy. Educational efforts aim to cultivate these qualities in citizens. Local cultural narratives offer potential resources for such endeavors. This qualitative research employs a hermeneutic approach to analyze the Bantarangin version of the Reyog Ponorogo story and its characters, particularly Prabu Klana Sewandana and Bujangganong. Dante's hermeneutic analysis methodology guides the data analysis, focusing on identifying the characters' embodied civic values and their alignment with established national character education principles. The study reveals that Reyog Ponorogo characters exemplify various citizenship values, including religious devotion, honesty, self-reliance, creativity, and patriotism. These values are demonstrably connected to the 18 national character values emphasized in Indonesian education. The article argues that the Reyog Ponorogo narrative offers valuable lessons for contemporary civic education. Integrating these themes into educational programs can cultivate a more responsible and engaged citizenry. Future research is recommended to explore the effectiveness of incorporating Reyog Ponorogo performances or workshops into curriculums. Investigating other local cultural narratives across Indonesia can further enrich civic education and foster appreciation for the nation's cultural diversity. Combining traditional cultural elements with modern educational practices can cultivate well-rounded citizens equipped to contribute meaningfully to society. This study contributes to the literature by integrating the local story into academic programs, cultivating a more responsible and engaged one.